Kandungan Nutrisi Black garlic Hasil Pemanasan dengan Waktu Berbeda: Nutrition content of Black garlic heated in different times - Nelwida, Nelwida; Berliana, Berliana; NURHAYATI, Nurhayati (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2019)
Garlic as feed additives have been widely used to increase animals performance due to it can help absorption process of nutrients so that it can spur animal growth and produce healthy products. Garlic is crushed or damaged easily and when is broken, some of these bioactive sulfur components produce a strong pungent odor. Black garlic is fresh garlic that has been fermented for a period of time. Black garlic is formed through heating and causing the garlic turn to black because of its browning compounds. Black garlic does not exude a strong off-flavor, like fresh garlic because of changes to the compound allicin, which is responsible for its odor. The study was done to measure the nutritional content on black garlic based on different times of heat treatment at 600C. The research design was complete randomized design (CRD) with 4 treatments and 5 replications. The treatments were time of heating; P0 (control, 0 day), P1 (15 days), P2 (30 days) and P3 (45 days) 500 g each. Parameters were moisture content, crude protein, ash, fat and carbohydrate. Data were analysed by analysis of variance, the significant effects were tested by Duncan’s multiple range test. To determine the best time of heating would be tested by Polynomial orthogonal. The results showed that different times of heat treatment significantly (P<0.05) affect nutrition of black garlic. Fifteen days of heating significantly incease moisture content but the moisture content decreased when heating was longer such as for 30 and 45 days. Longer time of heating increased significantly (P <0.05) the protein and fat content of black garlic, while the carbohydrate content significantly decreased (P <0.05). Polynomial orthogonal test resulted that the heating of garlic at 600C for 17 days gives the best nutrient content of black garlic. It was concluded that the length heating of garlic to produce the best nutrition content of black garlic was at a temperature of 600C for 17 days.